CP-132 Impact of pharmaceutical interventions in a medicine department. (14th February 2016) - Hebbinckuys, E Choquet; David, F; Merger, D; Alba, J
Abstract : Background: Pharmacists play an important role by assuring and improving the quality and safety of the medication circuit, especially through pharmaceutical approval. In our hospital, only 20% of prescriptions are analysed by pharmacists because the pharmacy service suffers from a lack of clinician pharmacists. Purpose: In order to enhance our pharmaceutical validation activity, we analysed our different pharmaceutical interventions and evaluated the pharmacoeconomic impact. Material and methods: A prospective study was conducted in a polyvalent medicine unit for 3 months. Every prescription was analysed by a pharmacist and its interventions were categorised into several categories (aim and type of intervention). The percentage change in prescription following our intervention was assessed and the economic outcome was estimated from the daily cost of treatment change or discontinuation. Results: The total number of prescription lines analysed was 6857, with 187 interventions; 50% of interventions were effective. 54% of pharmaceutical interventions aimed at switching from the intravenous (IV) to the oral route and represented the majority of savings (1200€ of 1270€ saved). A high proportion of patients receive IV therapy although this may be inappropriate. Among all pharmacist interventions, 20% recommended a dose adjustment: 40% of them were related to adaptation to kidney function (13% were followed), 26% concerned sub-therapeutic doses (40% were followed) and 34% concerned overdoses (77% followed). 11% of pharmaceutical interventions concerned substitution proposition (acceptance of only 21%); this probably leads to therapeutic failure and could lead to undesirable events. The rest of the indications related to therapeutic duplication (8%), difference in personal treatment (4%), association had no indicated (2%) and contraindication (1%). Not many of these interventions were followed, excepted in the last two categories. Conclusion: Pharmacists' interventions appear to result in an appropriate prescription and improve the safety of drug therapies. They generate financial savings due to reduction in unnecessary therapy. In the future, we should encourage a dialogue with prescribers. Extrapolation of the results should be performed to present a real financial and medical impact of the pharmaceutical interventions and to obtain a dedicated full time clinician pharmacist. References and/or Acknowledgements: Validation pharmaceutique des prescriptions hospitalières. Presse Médicale August 2005 No conflict of interest.